PENGARUH RAGAM METODE MENGAJAR GURU PAI TERHADAP MOTIVASI BELAJAR SISWA KELAS XI IPA MA. AL-QODIRI JEMBER TAHUN PELAJARAN 2018/2019: Muhamad Ansori, M.Pd.I, Institut Agama Islam (IAI) Al-Qodiri Jember - Muhamad Ansori (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2019)
This research aims to: Knowing the variety of teaching methods PAI teacher class XI IPA MA students. Al-Qodiri Jember Academic Year 2018/2019, (2) motivation class XI IPA MA students. Al-Qodiri Jember Academic Year 2018/2019, (3) the effect of variations of PAI teacher teaching methods to motivate students XI IPA MA students. Al-Qodiri Jember Academic Year 2018/2019 lesson. In this research using quantitative descriptive, method product moment. The population of this research is class XI IPA MA students. Al-Qodiri Jember Academic Year 2018/2019 numbering 92. After analyzing the data collected, it was found that (1) the variation of teaching methods PAI teacher XI IPA MA students. Al-Qodiri Jember Academic Year 2018/2019 is very good. (2) Motivation class XI IPA MA students. Al-Qodiri Jember is very good. (3) There is a variety of teaching methods influence on the motivation of teachers PAI XI IPA MA students. Al-Qodiri Jember Academic Year 2018/2019 by 36.3%.